Development and validation of RP-HPLC method for determination of content uniformity of rabeprazole sodium in its tablets dosage form - S. Elumalai, Kiran Aher, Girija Bhavar, Sachin Gupta (Journal of Applied Pharmaceutical Science)
The aim of the present work was to develop simple, shorter and effective HPLC method with UV detection (285nm) and subsequent validation for the content uniformity determination of Rabeprazole Sodium in marketed tablet samples. The method uses isocratic mobile phase of 0.1M sodium phosphate buffer (pH adjusted to 6.5 with sodium hydroxide solution) and acetonitrile 65:35 compositions on reverse phase Lichrosphere RP-100 C8 column. The RSD was observed to 0.21 percentage and linearity range of (LOQ) 0.025 – 150 percentage of label claim established with 0.9999 correlation, 8 different brands marketed samples were successfully analysed for content uniformity and compared the results with the USP and other guidelines for acceptance criteria. The developed method was found precise, linear, rugged and robust for validated parameters. The method can be used for assay and the content uniformity determination of Rabeprazole Sodium in its tablet dosage form.
Keywords: Rabeprazole sodium,Content uniformity test,Tablet dosage form, Market sample analysis.